(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the associations of prognostic nutritional index and hemoglobin-to-red cell distribution width with hospitalization risk and to develop a predictive model for hospitalization in hemodialysis patients. Methods: A retrospective study was conducted in 157 hemodialysis patients. Hospitalization, defined as at least one hospital admission during the study period, was the primary outcome. Multivariable logistic regression was used to identify independent predictors of hospitalization. Model performance was assessed using the Hosmer-Lemeshow test and forest plots. Results: The mean age was 53.4 ± 14.2 years, and 53.5% of patients were male. The hospitalization rate was 54.7%, with cardiovascular disease being the leading cause (56.4%). Patients who were hospitalized had significantly lower prognostic nutritional index values than those who were not hospitalized (p = 0.014). In the multivariable model, prognostic nutritional index was independently associated with hospitalization risk (OR = 0.93; 95% CI: 0.87-1.00; p = 0.05), whereas hemoglobin-to-red cell distribution width and other covariates were not statistically significant. The model demonstrated good discrimination. Conclusions: Prognostic nutritional index is a simple, low-cost marker and an independent predictor of hospitalization in patients undergoing maintenance hemodialysis.